Answer:
Step-by-step explanation:
Reduce the redundancy of information to the following:
"find the equation of the line through (-6, 5) and (-3, -3)."
Use the point-slope formula y = mx + b and the given points to determine the slope, m, and the y-intercept, b:
Point (-6, 5): y = 5 when x = -6: 5 = m(-6) + b Equation 1
Point (-3, -3): y = -3 when x = -3: -3 = m(-3) + b Equation 2
Subtracting Equation 1 from Equation 2 yields -8 = +3m and so m = -3/8
Then y = mx + b becomes y = (-3/8)x + b, and if we substitute the coordinates of the point (-3, -3) into this equation, we can solve for b:
-3 = (-3/8)(-3) + b, or -3 = 9/8 + b, or-24/8 = 9/8 + b
The latter equation simplifies to -33/8 = b, and so the equation through the first two points is
y = (-3/8)x - 33/8 or y = (-3/8)[x + 11]